Emission spectra and current characteristics of negative corona discharge in an electrode system with liquid anode - Bolotov, O.V.; Golota, V.I.; Taran, G.V. (Вопросы атомной науки и техники, 2020)
Experimental study of emission spectra and current characteristics of negative corona discharge over the surface of aqueous salt solutions have been carried out. The radiation spectra from the active zone of the discharge in the wavelength range 200…600 nm were obtained and identified. It was found that most of the spectral lines correspond to the lines of second positive system of molecular nitrogen. The spectral lines of the nitrogen ion N₂⁺ and the lines corresponding to the emission of the OH radical in the UV spectral region are also observed.Current-voltage characteristics of the discharge were obtained at the non-stationary and diffuse stages of the discharge. It was shown that obtained current-voltage characteristics are in good agreement with the results of theoretical calculations using the Townsend expression.